A Neonate with CLOVES Syndrome. (21st October 2014) - Sarici, Dilek; Akin, Mustafa Ali; Kurtoglu, Selim; Tubas, Filiz; Sarici, Serdar Umit
Abstract : Congenital lipomatous overgrowth, vascular malformations, and epidermal nevi (CLOVE) syndrome is a recently delineated disorder that comprises vascular malformations (typically truncal), dysregulated adipose tissue, scoliosis, enlarged bony structures (typically of the legs) without progression, or distorting bony overgrowth. The name CLOVE was subsequently extended to CLOVES to emphasize the association with scoliosis/skeletal and spinal anomalies and seizures/central nervous system malformations. We herein report a very rare case of CLOVES syndrome with the findings of lipomatous overgrowth in the cheek (facial asymmetry), vascular malformation (hemangiomas), epidermal nevi (large port wine stains), and skeletal abnormalities (widened first interdigital space, dystrophia in the nail of the first digit of the right foot, and bilateral hypertrophy of the first digits of the feet).